Dielectric function of palladium capped zirconium thin films as a function of absorbed hydrogen. (31st August 2017) - Azofeifa, Daniel E.; Clark, Neville; Vargas, William E.; Solis, Hugo; Avendano, E.; Cambronero, Michael; Valverde-Mendez, Diana
Abstract: We report measurements of the optical transmission, between 240 and 1040 nm, and electrical resistivity of polycrystalline zirconium thin films as they absorb hydrogen. Both are measured as H2 pressure is increased up to 880 mbar, at room temperature. Films, 20–22 nm thick, are deposited on fused quartz substrates by e-beam evaporation at 5.3 × 10 −7  mbar base pressure and covered with a 8.0 nm Pd over-coat. The morphology of the films is studied by means of AFM images. The complex refractive indices of Zr and Pd are extracted numerically from the transmission spectra by using a spectral projected gradient method for different hydrogen pressures. The corresponding dielectric functions for various Zr hydrogen concentrations are described with the parametric Drude-Lorentz and Brendel-Bormann (DL & BB) models. The Acceptance-Probability-Controlled Simulated Annealing approach is applied to calculate the parameters of the DL & BB model. This allows us to describe the effect of increasing hydrogen absorption on these parameters and in derived quantities, like the relaxation time and the effective mass of conduction electrons, the electrical resistance, the Fermi energy, and the electronic density of states at the Fermi level. Highlights: Transmission (240–1040 nm) of Zr thin film exposed to H2 atmosphere is presented. Dielectric function inverted from transmission data of hydrogenated films is given. These data is described with the parametric DL & BB models for some H2 pressures. Effect of hydrogen absorption in model's parameters is shown.